Lifelong learning dimensions and their associations with late-life cognitive decline: moderating roles of socioeconomic status and early life education - Zheng, Feiran (Frontiers in Psychology, 2025)
IntroductionAmidst the global wave of population aging, safeguarding cognitive health in older adults is a pressing public health issue. However, the key components of lifelong learning and whether its benefits apply universally across social backgrounds remain unclear. This study aimed to identify distinct dimensions of lifelong learning and to test their effects on subjective cognitive function, as well as the moderating role of socioeconomic background.MethodsWe conducted a cross-sectional survey of 278 Chinese older adults aged 60 and above. Exploratory factor analysis was used to delineate the dimensions of lifelong learning. Hierarchical regression analysis was then employed to assess the predictive effects of these dimensions on subjective cognitive function and the moderating effects of socioeconomic status (SES) and early-life education (ELE).ResultsTwo distinct dimensions were identified: “information-driven cognitive engagement” and “social interaction and experiential learning.” Only the former, characterized by cognitively challenging activities, showed a significant positive predictive effect on subjective cognitive function (β = 0.143, p = 0.017). Crucially, neither SES nor ELE significantly moderated this relationship.DiscussionThe findings suggest that the cognitive benefits of challenging learning activities are broadly universal, transcending socioeconomic and educational divides. This “equitable benefit” provides strong empirical evidence for policy shifts from encouraging generalized “participation” to promoting inclusive and deep “cognitive engagement,” thereby fostering fairer and more effective cognitive health promotion strategies for older adults.